Pseudohypertriglyceridemia: A Novel Case with Important Clinical Implications. (6th August 2020) - Rughani, Ankur; Blick, Kenneth; Pang, Hui; Marin, Monica; Meyer, Jonathan; Tryggestad, Jeanie B.
Abstract : Pseudohypertriglyceridemia is an overestimation of serum triglyceride levels that may incorrectly lead to a diagnosis of hypertriglyceridemia. Glycerol kinase deficiency is a condition in which glycerol cannot be phosphorylated to glycerol-3-phosphate, resulting in elevated levels of serum glycerol. Laboratory assays that measure triglycerides indirectly may be affected by elevated glyerol levels and incorrectly report serum tryglyceride levels. We present a case of a novel missense mutation in the GK gene leading to isolated glycerol kinase deficiency and pseudohypertriglyceridemia in a male infant of a mother with gestational diabetes. This paper reviews glycerol kinase deficiency, describes the challenges in diagnosing pseudohypertriglyceridemia, and provides suggestions on improving diagnostic accuracy. Additionally, a potential maternal-fetal interaction between gestational diabetes and glycerol kinase deficiency is discussed.